ANALISA KEBERHASILAN DIPLOMASI OLAHRAGA INDONESIA UNTUK MEMASUKAN PARALAYANG KE DALAM ASIAN GAMES 2018 - Fathan Yuda Febrianda, (2021)
This thesis research sport diplomacy by Indonesia to supporting inclusion of paragliding on Asian Games 2018. Indonesia decided to include paragliding on Asian Games 2018 because they view it as potential sport since it has ability to gained good results and event organizing by its communities. Besides that, Indonesia must gained an approval from overseas related sport communities that handle Asian Games and paragliding activities. The research on this thesis use Diplomacy Theory, Sport Diplomacy Concept, Soft Power Concept, and Multi-Track Diplomacy Concept. Besides that, the research also use qualitative method with case studies approach and descriptive motive. The diplomacy accomplishment will be determent by the Indonesia's International Relations Index. The research founds that Indonesia has prepared their sport diplomacy activity by employing highly qualified individuals, strengthening its internal support, and gaining support and approval from overseas related sport communities such as OCA, Global and Asia's Aero Sport Organizations, and Asia's paragliding communities. The sport diplomacy by Indonesia has given positive result for Indonesia in Asian Games 2018 because it generate decent amount of medals for Indonesia, exposing Indonesia best paragliding result to Indonesian Societies, and increase Indonesia's image on Global Paragliding communities. In conclusion, The sport diplomacy by Indonesia to include paragliding has complete its goals and it also implemented international realitionship teory and concepts and index values.